A gestão da demanda em cadeias de suprimentos: um estudo no setor atacadista distribuidor de produtos de mercearia básica - Melo, Daniela de Castro (2011)
Demand management is an emerging topic in supply chain management. It is focused on a fast and adequate integration of supplier needs in order to balance and strategically align demand with operational capability in the supply chain. The lack of demand alignment deals with problems in supply chain, which leads to inefficient customer service, poor stock rotation, and high obsolescence rate aggravated by the wide diversity of products. The objective of this thesis was to develop a framework for demand management in the supply chain of grocery products considering the dyadic relationship between the supplier and the wholesale. The research revealed that the framework can be divided into 1) determining factors for the implementation of demand management between the wholesale and supplier and 2) the implementation process of the demand management between these firms. The determining factors involve strategic intent; internal alignment of the strategic policies; supplier segmentation; customer segmentation; reward, expertise, legitimate power and collaborative supply chain orientation. The implementation of this process can be divided into three phases: 1) joint alignment of strategic policies, 2) formulation of business plan and 3) implementation and monitoring of the business plan. Moreover, this process has four elements that permeate it: top management involvement, inter and intra-firm interactions, challenges and benefits of demand management. The benefits reflect on a reduction of the effect of the demand amplification, profitability by improving efficiency and effectiveness, as well as knowledge sharing and learning.